Batal Demi Hukum: Poligami Tanpa Persetujuan Isteri: Studi Kasus POLDA Provinsi Maluku Utara - Muhammad Zaber Wahid; Baharuddin Hi. M.A Hi. Abdullah (Indonesian Journal of Shariah and Justice, 2021)
Marriage Law in Indonesia adheres to the principle of Monogamy. That is, a husband can only have a wife. But in the applicable law, polygamy is possible on several conditions including a wife's license and authorized by the court. In practice, many polygamy practices carried out without the wife's knowledge are even done "sirri" or nikah under the hands. This research aims to analyze the practice of polygamy without the consent of one party in the perspective of civil law and Islamic law in the city of Ternate, how the legal settlement of marriage cases without the consent of one party in the North Maluku police and the religious court of Ternate city, the purpose of the study to analyze marriage (Polygamy) without the consent of either party in the perspective of Civil Law and Islamic Law. This research uses a type of skinative research with an analytical descriptive model which is then combined with normative studies. The study found that marriages (polygamy) performed without the first wife's knowledge were said to be null and void because they did not meet the elements set by law and courts.